Analisis Pengaruh Kinerja Aparatur Dan Tingkat Pendidikan Dalam Rangka Meningkatkan Kualitas Pelayanan Kecamatan Lenteng Kabupaten Sumenep Yang Dimediasi Oleh Produktivitas Kerja - Hosnan Hosnan; Hadi Susanto; Sri Mulyani (Journal of Management and Creative Business, 2023)
The results showed that: 1) Apparatus performance had a significant positive effect on service quality with an original sample value of 0.211. 2) Apparatus performance has a significant positive effect on work productivity with an original sample value of 0.340. 3) The level of education has a significant positive effect on service quality with an original sample value of 0.389. 4) The level of education has a significant positive effect on work productivity with an original sample value of 0.608. 5) Work productivity has a significant positive effect on service quality with an original sample value of 0.402. 6) Apparatus performance has a significant positive effect on service quality mediated by work productivity with an original sample value of 0.769. 7) The level of education has a significant positive effect on service quality mediated by work productivity with an original sample value of 0.863.